ANCIENT COSMOLOGIES ([S.l.])
1 online resource
Keywords: In Ancient Cosmologies (1975) nine eminent scholars seek to answer the question, what was the shape of the universe imagined by those ancient peoples to whom all modern knowledge of geography and astronomy was inaccessible? How did the ancient Egyptians, Babylonians, Jews, Indians, Chinese, Arabs, Greeks and Norsemen conceive the form of the cosmos which accommodated not only the known face of the earth and the visible heavenly bodies but also those other worlds which it was deemed necessary to locate comprehensibly in space - the realms of the dead, both blessed and damned, and the countries inhabited by gods and demons?